(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
Abstract: this article examines the structure of sentences in English and Uzbek languages, focusing on the primary and secondary parts of the sentence. It explores the similarities and differences in the way these languages organize and express ideas through their respective sentence structures. The article provides a detailed analysis of the key components that make up a sentence in each language, highlighting the roles and functions of the primary and secondary parts. By comparing the sentence structures across these two languages, the article aims to contribute to the understanding of cross-linguistic variations and the underlying principles governing sentence formation.